Use of the national electronic maternal and child health registry (MCH eRegistry) in primary care clinics in occupied Palestinian territory: a pilot time-motion study. (March 2019) - Awwad, Tamara; Venkateswaran, Mahima; Lindberg, Marie Hella; Abu Khader, Khadija; Hijaz, Taghreed; Ghanem, Buthaina; Mørkrid, Kjersti; Ramlawi, Asad; Salman, Rand; Frøen, J Frederik
Abstract: Background: In primary care maternal and child health clinics in occupied Palestinian territory, documentation and reporting consume considerable time for care providers. An electronic maternal and child health registry (MCH eRegistry), with point-of-care clinical decision support, is being implemented nationally in governmental clinics. We conducted a pilot study of time spent by care providers on important tasks, in preparation for a trial to compare eRegistry and non-eRegistry clinics. Methods: We conducted semi-structured interviews of ten nurse-midwives from six governmental clinics in the West Bank to map clinical workflows, and developed a data collection tool for time-motion observations. In May, 2017, observers recorded one workday in three eRegistry and three non-eRegistry clinics. For each consultation, we calculated the median time spent (in minutes) on each task, and then compared time spent in eRegistry and non-eRegistry clinics using Wilcoxon rank-sum tests. Ethics approvals were obtained from the Palestinian Health Research Council and Regional Ethics Committee, Norway. Informed consent was obtained from all pregnant women. Findings: Twelve antenatal consultations (four first booking visits, eight follow-up visits) were observed in eRegistry clinics and 39 (four first visits, 35 follow-up visits) in non-eRegistry clinics. The median duration of booking visits was 19·9 min (IQR 12·9) in eRegistry clinics and 22·1 min (24·9) in non-eRegistry clinics. In eRegistry clinics, the median duration of follow-up visits was 14·6 min (17·3), of which the median clinical examination time was 1·7 min (0·6) and median health information management time was 5·3 min (5·8). In non-eRegistry clinics, the median duration of follow-up visits was 8·8 min (8·7), of which the median clinical examination time was 2·5 min (2·9) and health information management time was 4·6 min (2·0). This pilot study was not sized for comparisons; health information management time was not statistically different between groups (p=0·1). Interpretation: Health information management constituted large parts of limited antenatal consultation time. The pilot provided data to estimate that the upcoming trial must include a sample of 24 clinics and 210 observations, with similar proportions of booking and follow-up consultations in both arms, to observe meaningful differences in time consumption with sufficient statistical power. Funding: European Research Council and Research Council of Norway.